PENGEMBANGAN BUKU TEKS DIGITAL INTERAKTIF UNTUK PEMAHAMAN KONSEP GEOGRAFI - Suryani, Nani (Jurnal Gea, 2015)
The research aims to develop Interactive Digital Textbooks for Geography concept understanding on the topic of the Environment by adopting R&D (Research and Development) method. The design of Interactive Digital Textbooks was validated by three validators, namely two validators for content and one validator for the media. To find the effectiveness of the Interactive Digital Textbooks, an experiment with randomized control group pretestâposttest design was employed. Meanwhile, the research subjects for the product testing were the eleventh grade students of UPI (Indonesia University of Education) Laboratory Senior High School.Â  Based on empirical test, it is found that there was a difference in experimental class studentsâ scores before and after treatment with Interactive Digital Textbooks I and II. The difference was evidenced in the increased average score after the treatment. It is also found that there was a difference in control class studentsâ test results before and after treatment with conventional Textbooks I and II. The difference is showed by increased average score after treatment. Furthermore, there was a difference in concept understanding between experimental class students who used Interactive Digital Textbooks I and II and those of the control class treated with Textbooks I and II. The difference suggests that there was improvement in the concept understanding of both experimental and control class students. Hence, the developed Interactive Digital Textbooks had influence on studentsâ concept understanding in Geography subject.Keywords: interactive digital textbooks, concept understanding.